Peningkatan Kemampuan Kontrol Diri Siswa dengan Pemberian Konseling Kelompok dan Konseling Individual - Murni Dahlena Nst; Sri Ugika Wulandari; Jamilah Harahap; Yentiarsini Yentiarsini (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The purpose of this study is to improve students' self-control skills by providing group counseling and individual counseling. The method used is a literature study and data is obtained by reviewing literature using references from various sources including articles, journals, and related research results. The results showed that improving students' self-control skills by providing group counseling and individual counseling is that the Guidance and Counseling (BK) teacher can provide group guidance services. Through these two services, BK teachers can make a significant contribution in shaping students into individuals who have strong self-control and are able to manage their behavior wisely. The role of parents in controlling and developing students' self-control is very important. Without parental support and involvement, efforts to improve students' self-control can experience obstacles.